2020
DOI: 10.1002/cplu.202000131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Chemical Compositions of Bismuth Oxyiodides on the Electroreduction of Carbon Dioxide to Formate

Abstract: Bismuth oxyiodides with varying chemical compositions were fabricated to effectively electrochemical reduce CO 2 to formate. Bi 5 O 7 I and Bi 7 O 9 I 3 nanosheets assemble irregularly, and BiOI nanosheets form a sphere-like structure. Compared with BiOI and Bi 7 O 9 I 3 , Bi 5 O 7 I exhibits an excellent Faradaic efficiency of 89 % for formate production with the partial current density of 13.2 mA/cm 2 at À 0.89 V vs. RHE owing to the elevated amounts of Bi metal sites reduced from Bi 3 + during electrolysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…The electrocatalytic CO 2 reduction reaction (CO 2 RR) refers to the electrochemical reduction of CO 2 to desired products, 9 e.g. C1 products (carbon monoxide, 10 formic acid, 11,12 methanol, 13 methane [14][15][16] ), C2 products (ethylene, [17][18][19][20] ethanol [21][22][23] ), and C3 products (propanol 24 ). The first step of CO 2 RR is the activation of CO 2 into a radical intermediate.…”
Section: Electrochemical Conversion Of Co 2 To Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrocatalytic CO 2 reduction reaction (CO 2 RR) refers to the electrochemical reduction of CO 2 to desired products, 9 e.g. C1 products (carbon monoxide, 10 formic acid, 11,12 methanol, 13 methane [14][15][16] ), C2 products (ethylene, [17][18][19][20] ethanol [21][22][23] ), and C3 products (propanol 24 ). The first step of CO 2 RR is the activation of CO 2 into a radical intermediate.…”
Section: Electrochemical Conversion Of Co 2 To Carbonmentioning
confidence: 99%
“…BMIm] − CO → [BMIm]carbene + CO ads(11) CO ads + e − + H 2 O → COH ads + OH −(12)COH ads + e − → C ads + OH −…”
unclassified
“…For example, the grain boundary-enriched Bi catalyst showed a high current density (450 mA cm −2 ), FE (97%), and stability (100 h) toward ultra-high concentration of HCOOH (up to 100 wt%). 18 Han et al 19 observed 100% FE at −1.3 V vs. SCE for Bi nanosheet electrodes, whereas bismuth oxyiodides prepared by Wang et al , 20 have shown high current density (40 mA cm −2 ) at −0.9 V vs. RHE for HCOO − production. Besides, many continuous flow reactors deliver current density over 100 mA cm −2 and lifetime (h to a several months) with a high selectivity of HCOO − /HCOOH products.…”
Section: Introductionmentioning
confidence: 99%